The effects of strategic and employee factors on the project performance of Iraqi public construction projects:the role of knowledge transfer, experience and safety - Obaid, Mohammed Hatem (Tanjong Malim, 2019)
The effects of strategic and employee factors on the project performance of Iraqi public construction projects:the role of knowledge transfer, experience and safety by Obaid, Mohammed Hatem